Inhibitory effect of capsaicin on B16-F10 melanoma cell migration via the phosphatidylinositol 3-kinase/Akt/Rac1 signal pathway - Shin, Dong-Hoon; Kim, Ok-Hee; Jun, Hye-Seung; Kang, Mi-Kyung (Experimental & molecular medicine, 2008)
Capsaicin ( trans -8-methyl- N -vanillyl-6-nonenamide), the major pungent ingredient of red pepper, has been reported to possess anti-carcinogenic and anti-mutagenic activities. In this study, the anti-migration activity of capsaicin on highly metastatic B16-F10 melanoma cells was investigated. Capsaicin significantly inhibited the migration of melanoma cells without showing obvious cellular cytotoxicity at low doses. This effect correlated with the down-regulation of phosphatidylinositol 3-kinase (PI3-K) and its downstream target, Akt. Although B16-F10 cell migration was increased by the PI3-K activator through the activation of Akt, these PI3-K activator-induced phenomena were attenuated by capsaicin. Moreover, capsaicin was found to significantly inhibit Rac1 activity in a pull-down assay. These results demonstrate that capsaicin inhibits the migration of B16-F10 cells through the inhibition of the PI3-K/Akt/Rac1 signal pathway. The present investigation suggests that capsaicin targets PI3-K/Akt/Rac1-mediated cellular events in B16-F10 melanoma cells. Consequently, capsaicin administration should be considered an effective approach for the suppression of invasion and metastasis in malignant melanoma chemotherapy.